The relationship between teacher–student relationships and academic grades among Chinese rural high school students: the moderating role of mental health symptoms and the conditional moderating effect of academic resilience - Chen, Xiaohui; Bailey, Richard Peter; Yin, Xiaojiao; Samsudin, Nadia (Frontiers in Psychology, 2024)
Objective: This study examines the relationship between Teacher-Student Relationships and academic grades among Chinese rural high school students, focusing on the moderating role of mental health symptoms and the conditional moderating effect of academic resilience.Method: A moderated moderation analysis was conducted via Mplus on data collected from a sample of rural Chinese high school students. SEM was used to test the direct and interactive effects of these variables on academic outcomes.Results: Teacher-Student Relationships were found to have a significant positive association with students' academic grades. Academic resilience plays a conditional moderating role, with students who have higher levels of resilience better able to maintain their academic performance, even when facing psychological distress. This suggests that resilience can buffer the impact of challenges, enhancing the positive influence of TSRs on academic outcomes.